Estrategias discursivas, redes sociales y su impactoen la subjetividad juvenil en el capitalismo 2.0 - Silva, Horacio (REVISTA JURÍDICA UNIVERSIDAD NACIONAL DEL OESTE, 2025)
This article examines how the new radical right employs discursive strategies and the intensive use of social media to exert ideological influence, particularly on young people. It also explores the impact of these dynamics on the construction of subjectivities and the mental health of those exposed to such discourses. The implications of these tactics are analyzed, and possible responses are proposed to counter hate speech within the context of platform capitalism. Through a theoretical and bibliographic analysis, key concepts are explored regarding social discourse, religious instrumentalization, and virality on social networks. Evidence is presented of the use of polarizing narratives, the dehumanization of opponents, and the exaltation of individualism as mechanisms to legitimize exclusionary policies.